Once-weekly teriparatide in hemodialysis patients with hypoparathyroidism and low bone mass: a prospective study. Issue 4 (April 2016) - Sumida, K.; Ubara, Y.; Hoshino, J.; Mise, K.; Hayami, N.; Suwabe, T.; Kawada, M.; Imafuku, A.; Hiramatsu, R.; Hasegawa, E.; Yamanouchi, M.; Sawa, N.; et al.
Abstract Summary Once-weekly 56.5-μg teriparatide treatment was significantly associated with the increase in lumbar spine bone mineral density at 48 weeks among hemodialysis patients with hypoparathyroidism and low bone mass; however, discontinuation of treatment because of adverse events was frequently observed. Careful monitoring for adverse events should be required. Introduction Once-weekly 56.5-μg teriparatide is reportedly effective for treating osteoporotic patients without renal insufficiency. However, little is known about the efficacy and safety of once-weekly teriparatide in hemodialysis patients. Methods We conducted a 48-week prospective, observational cohort study including 22 hemodialysis patients aged 20 years or older with hypoparathyroidism and low bone mass who received once-weekly teriparatide at 56.5 μg at a tertiary care hospital between January 2013 and January 2015. Primary outcomes were within-subject percent changes of bone mineral density (BMD) at the lumbar spine, femoral neck, and distal one-third radius at 24 and 48 weeks. Secondary outcomes included percent changes of serum bone turnover markers (osteocalcin, bone-specific alkaline phosphatase (BAP), N-terminal propeptide of procollagen type 1 (P1NP), and tartrate-resistant acid phosphatase 5b (TRAP-5b)). Adverse events were evaluated. Results The BMD increased at the lumbar spine by 3.3 ± 1.9 % (mean ± SEM) and 3.0 ± 1.8 % at 24 and 48 weeks but not in the femoral neck and distal one-third radius. Serum osteocalcin, BAP, and P1NP increased significantly at 4 weeks, maintaining higher concentrations up to 48 weeks, although TRAP-5b decreased gradually during treatment. The baseline BAP was significantly associated with the 48-week percent change in lumbar spine BMD. Transient hypotension was the most common adverse event. Ten patients discontinued treatment because of adverse events. Conclusions Once-weekly teriparatide was associated with increased lumbar spine BMD in hemodialysis patients with hypoparathyroidism and low bone mass. Careful monitoring should be required for treatment of such patients.